Side Effect of Inter-Time Replacement: Members of the House of Representatives by Political Parties in a Democratic System - Hasyim, Hafid; Hasanah, Siti; Jiwantara, Firzhal Arzhi; Pratama, Inka Nusamuda (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
Sovereignty is fully in the hands of the people and implemented according to the Constitution the mechanism for implementing people's sovereignty is through general elections elected by the people in the context of implementing the democratic system in Indonesia, but the mechanism for the Interim Replacement of members of the People's Representative Council/Regional People's Representative Council as stipulated in Article Law Law Number 17 of 2014 concerning the MPR, DPR, DPD, Provincial DPRD and Regency/Municipal DPRD provides an opportunity to abort elected DPR members. The purpose of this study is to determine the side effect of the interim replacement of members of the DPR by political parties in a democratic system. The research method used is a qualitative research method by analyzing phenomena. The results of research on the side effect of inter-time replacement in the democratic system for members of the DPR which are carried out by political parties tend to be based on the interests of political parties, not based on the interests of the people, so this has a side effect of weakening the democratic system where people's votes from general election results are not a priority, this because the inter-time replacement process for members of the DPR is carried out in full and becomes the authority of political parties. Therefore strengthening the inter-time replacement mechanism is necessary so that the political rights of the community can be properly protected.